Teacher’s Perception Over Identity Negotiation of Immigrant Children in Secondary Schools in the UK - Muhammed, Sule Sallah (European Journal of Applied Sciences, 2023)
This study explores the intricate connection between identity negotiation and academic achievement among immigrant students in high schools in the United Kingdom. It examines how students and teachers navigate cultural diversity’s challenges in education, uncovering the interplay between cultural backgrounds, language learning, and academic success. Utilizing mixed methods, the research employs interviews and observations to collect data from immigrant students and teachers across four urban high schools. Findings reveal the time-intensive nature of language acquisition for immigrant students, impacting their academic language proficiency over the years. Teachers are crucial in establishing inclusive classrooms that foster identity negotiation and academic excellence. The study underscores the importance of effective school-family communication, advocating tailored approaches for cultural differences. Implications extend to educational policy, emphasizing inclusive environments that value students’ diverse identities. Providing insights into immigrant students’ experiences, this research enriches the understanding of identity negotiation in education and offers actionable recommendations for enhancing their academic achievement.